PENGARUH BESARAN PERUSAHAAN, LEVERAGE, FREE CASH FLOW, PROFITABILITAS DAN KUALITAS AUDIT TERHADAP MANJEMEN LABA RIIL - Ning Dyah Utami; Sri Handayani (Diponegoro Journal of Accounting, 2019)
This research aims to analyze the influence of company characteristics on real earnings management. Company characteristics in this study are firm size, leverage, free cash flow, profitability and audit quality.The population of this study are manufacturing companies listed on the Indonesia Stock Exchange for the period 2013-2017. Based on the methods of data collection used in this study is purposive sampling method, there are 490 total observational data. This research analyzes the disclosure of company characteristics in real earnings management with 3 methods of Abnormal Cash Flow From Operations, Abnormal Production Cost, and Abnormal Discretionary Expense. Multiple linear regression analysis was used as the primary tool of analysis in this research.The results of this study indicate that firm size and free cash oflow has a significant influence on real earnings management. However, leverage, profitability and audit quality have no significant effect on real earnings management.